A Pre-season Comparison of Aerobic Fitness and Flexibility of Younger and Older Professional Soccer Players - Signorelli, G. R.; Perim, R. R.; Santos, T. M.; Araujo, C. G. (International Journal of Sports Medicine, 2012)
Aerobic fitness and flexibility generally present age-related decreases, yet the influence of age on these variables in soccer players is still unknown. We obtained oxygen consumption (VO2) and heart rate (HR) at 12 km · h − 1, anaerobic threshold and maximum intensities, and athletes’ flexibility profiles using Flexitest (FLX). Pre-season data (2005–2011) from the 2 extreme age terciles (n=54) – YOUNGER (17–22 years old) and OLDER (27–36 years old) – of a group of 162 players from an elite Brazilian soccer club were compared. The effects of aging were also assessed by contrasting VO2, HR and FLX linear regressions – slope and intercept – vs. age-predicted and reference values. The results were similar between the YOUNGER and OLDER terciles for VO2max, at 62.7±6.1 vs. 63.2±6.2 mL · kg − 1 · min − 1, respectively (p=0.67), effect size (ES)=0.08, and for FLX, at 43±5.9 vs. 41±6.0, respectively (p=0.11, ES=0.34); the YOUNGER tercile exhibited higher values for HRmax than the OLDER tercile, at 194±8.1 vs. 189±8.8 b · min − 1, (p<0.01, ES=0.59). Players in the OLDER tercile did not present an age-predicted decrease in VO2max, whereas HRmax and FLX diminished with age as predicted. We conclude that, at least for these variables, younger and older players were effectively identical in their pre-season levels of conditioning.
Keywords: sports; cardiopulmonary exercise testing; Flexitest; heart rate